PENINGKATAS KUALITAS PUBLIKASI ILMIAH DOSEN MELALUI PELATIHAN BIBLIOMETRIK PADA STAI NUSANTARA BANDA ACEH - Mulia Rahman, Mulia Rahman; Jasmadi; Reza Muttaqin; Muhammad Yusuf Zulkifli; Muslem; Hartati; Wahyu Khafidah; Nurhayati; Fadhillah; Syafrizal (Saweu: Jurnal Pengabdian Kepada Masyarakat, 2024)
Scientific publication is one of the main indicators in assessing the academic quality of a lecturer and higher education institution. However, many lecturers still face obstacles in improving the quality and quantity of their publications. One solution to overcome this problem is to apply bibliometric methods in scientific research and publications. Bibliometrics is a data analysis technique that allows researchers to identify research trends, scientific collaboration, and the impact of publications. This community service activity aims to increase the capacity of STAI Nusantara Banda Aceh lecturers in scientific publications through bibliometric training. This training includes an introduction to the basic concepts of bibliometrics, the use of software such as VOSviewer and Publish or Perish, and publication strategies in reputable journals. The evaluation results showed that after attending the training, there was an increase in lecturers' understanding of bibliometric concepts as well as increased motivation in writing and publishing scientific articles. This activity is expected to contribute to improving the quality of scientific publications of lecturers and the academic reputation of STAI Nusantara Banda Aceh.